Organic Manure Significantly Promotes the Growth of Oilseed Flax and Improves Its Grain Yield in Dry Areas of the Loess Plateau of China - Xingkang Ma; Yuhong Gao; Bing Wu; Xingbang Ma; Yifan Wang; Bin Yan; Zhengjun Cui; Ming Wen; Xue Zhang; Haidi Wang (Agronomy, 2023)
Organic fertilizers could be useful for agricultural sustainability. Therefore, this study explored green cultivation techniques to improve the grain yield of oilseed flax in dry areas of the Loess Plateau of China. With no fertilization (CK) as the control, the effects of sheep manure (S1: 12.5 t ha−1; S2: 25 t ha−1), poultry manure (C1: 5.8 t ha−1; C2: 11.6 t ha−1), and chemical fertilizers (F1: N 112 kg ha−1, P 75 kg ha−1, K 67.5 kg ha−1; F2: N 225 kg ha−1, P 150 kg ha−1, K 135 kg ha−1) on the growth and development, the grain filling characteristics, and the yield of the Zhangya 2 oilseed flax (Linum usitatisimum L.) variety were compared and analyzed based on a two-factor split plot experiment. The results showed that the application of manure significantly increased the emergence rate (ER) of oilseed flax. Poultry manure increased plant height while sheep manure increased stem diameter. The dry matter production was higher in the 25 t ha−1 sheep manure treatment by 2.47–40.11% compared with that of the other treatments, and it promoted the distribution ratio of dry matter to grains after anthesis. The observed relationship was in accordance with that presented by the logistic equation between grain weight and days after anthesis, and there were significant positive correlations between the 1000-grain weight and the average filling rate (V-ave), the maximum filling rate (V-max), and the growth at the maximum filling rate (W-max). The application of organic manure accelerated the grain filling rate (GFR); under the treatment with 25 t ha−1 sheep manure, V-ave, V-max, and W-max increased by 4.84–22.72%, 1.16–17.54%, and 4.58–22.63%, respectively, and the grain yield and the net income per unit area increased by 6.35–39.25% and 3.04–95.07%, respectively, compared with those under the other treatments. Consequently, the treatment with 25 t ha−1 sheep manure can significantly promote the growth and development of oilseed flax plants, optimize the grain filling characteristics, and increase the grain yield and net income, making it a suitable fertilization technique for oilseed flax in dry areas of the Loess Plateau of China.